2016
DOI: 10.1093/jjco/hyw038
|View full text |Cite
|
Sign up to set email alerts
|

Urologic cancer in Taiwan

Abstract: For the past three decades, cancer is the number one cause of death in Taiwan. An increasing trend in the incidence of urologic cancers has also been noticed since 1979. In 2012, urologic cancer accounted for 10.0% of all the new malignant cases. Prostate, bladder and kidney cancers are the most common types. Metastatic prostate cancer still accounted for nearly 30% of new cases in Taiwan between 2004 and 2012. There are several specifically noticeable characteristics of urothelial carcinoma in Taiwan, associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 29 publications
2
48
1
Order By: Relevance
“…In our study, we demonstrated the correlations of MMP11 SNPs among UCC susceptibility, clinical status, disease prognosis and survival. Tobacco consumption and increasing age were suggested as major risk factors for bladder cancer carcinogenesis [3,7], and it was observed and suggested that the urothelial carcinoma is a male predominant disease [2]. In the current study, we found that there is no statistical significant in gender (p = 0.991) and tobacco consumption (p = 0.442) between the controls and the UCC patients ( Table 1), suggesting that the impact of sex difference and cigarette smoking to bladder cancer carcinogenesis may be limited in those individuals involved in our study (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we demonstrated the correlations of MMP11 SNPs among UCC susceptibility, clinical status, disease prognosis and survival. Tobacco consumption and increasing age were suggested as major risk factors for bladder cancer carcinogenesis [3,7], and it was observed and suggested that the urothelial carcinoma is a male predominant disease [2]. In the current study, we found that there is no statistical significant in gender (p = 0.991) and tobacco consumption (p = 0.442) between the controls and the UCC patients ( Table 1), suggesting that the impact of sex difference and cigarette smoking to bladder cancer carcinogenesis may be limited in those individuals involved in our study (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial cell carcinoma (UCC) of the urinary bladder cancer (UBC) is responsible for approximately 3.0% of all newly diagnosed cancer and 2.1% of all cancer deaths [1]. In Taiwan, urothelial carcinoma is the most common type of bladder cancer which accounts for 98.65% cases, with a male-to-female predominance ratio of 2.6:1 [2]. Increasing age is one of the major risk factors for bladder cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we also assessed the incidence and hazard ratio of prostate cancer by dividing the duration of follow-up into ≤ 1 year, 1-5 years, and > 5 years, respectively. In Taiwan, the reported incidence of prostate cancer was about 0.30/1000 person-years in 2012; therefore, we measured the incidence of prostate cancer in 1000 person-years [27]. The proportional hazard model assumption was also examined while using a test of scaled Schoenfeld residuals.…”
Section: Discussionmentioning
confidence: 99%
“…BLCA is the ninth‐most common malignancy and thirteenth‐most common cause of cancer death worldwide . In 2012, urologic cancer comprised ca 10% of all new malignant cases in Taiwan . In addition, a significant association has been observed between ingested inorganic As and risk of BLCA, as reflected in a significant excess of BLCA mortality .…”
Section: Introductionmentioning
confidence: 99%
“…21 In 2012, urologic cancer comprised ca 10% of all new malignant cases in Taiwan. 22 In addition, a significant association has been observed between ingested inorganic As and risk of BLCA, as reflected in a significant excess of BLCA mortality. 23 Similar increases in mortality due to bladder and kidney cancer have been reported among residents in an arseniasis-endemic area in southwestern Taiwan.…”
Section: Introductionmentioning
confidence: 99%